MICROWAVE DIELECTRIC CHARACTERIZATION OF POLAR PROTIC LIQUIDS USING TIME DOMAIN REFLECTOMETRY - ARUNA P. MAHAROLKAR; A. G. MURUGKAR; P. W. KHIRADE (International Journal of Pharma and Bio Sciences, 2014)
Dielectric measurement on binary mixtures of N-N Dimethylacetaamide (DMA) with nButanol have been carried out over the entire concentration range ( of 0.1 – 1 volume fraction) using Time Domain Reflectometry (TDR) technique at 303.15K temperature at which all measurements have been carried out at the microwave frequency range of 10 MHz to 20 GHz. The static dielectric constant, relaxation time, density, excess static dielectric constant, excess inverse relaxation time, Bruggeman factor, excess molar volume of binary mixtures over the entire concentration range were determined to explore the effect hetero molecular interaction. Excess parameters are fitted to Redlich– Kister equation.